Variable Ventilation Improved Respiratory System Mechanics and Ameliorated Pulmonary Damage in a Rat Model of Lung Ischemia-Reperfusion - Soluri-Martins, André; Moraes, Lillian; Santos, Raquel S.; Santos, Cintia L.; Huhle, Robert; Capelozzi, Vera L.; Pelosi, Paolo; Silva, Pedro L.; de Abreu, Marcelo Gama; Rocco, Patricia R. M. (Frontiers in Physiology, 2017)
Lung ischemia-reperfusion injury remains a major complication after lung transplantation. Variable ventilation (VV) has been shown to improve respiratory function and reduce pulmonary histological damage compared to protective volume-controlled ventilation (VCV) in different models of lung injury induced by endotoxin, surfactant depletion by saline lavage, and hydrochloric acid. However, no study has compared the biological impact of VV versus VCV in lung ischemia-reperfusion injury, which has a complex pathophysiology different from that of other experimental models. Thirty-six animals were randomly assigned to one of two groups: 1) ischemia-reperfusion (IR), in which the left pulmonary hilum was completely occluded and released after 30 min; and 2) Sham, in which animals underwent the same surgical manipulation but without hilar clamping. Immediately after surgery, the left (IR-injured) and right (contralateral) lungs from 6 animals per group were removed, and served as non-ventilated group (NV) for molecular biology analysis. IR and Sham groups were further randomized to one of two ventilation strategies: VCV (n = 6/group) [tidal volume (VT) = 6 mL/kg, positive end-expiratory pressure (PEEP) = 2 cmH2O, fraction of inspired oxygen (FiO2) = 0.4]; or VV, which was applied on a breath-to-breath basis as a sequence of randomly generated VT values (n = 1200; mean VT = 6 mL/kg), with a 30% coefficient of variation. After 5 minutes of ventilation and at the end of a 2-hour period (Final), respiratory system mechanics and arterial blood gases were measured. At Final, lungs were removed for histological and molecular biology analyses. Respiratory system elastance and alveolar collapse were lower in VCV than VV (mean ± SD, VCV 3.6 ± 1.3 cmH20/ml and 2.0 ± 0.8 cmH20/ml, p=0.005; median [interquartile range], VCV 20.4% [7.9-33.1] and VV 5.4% [3.1-8.8], p=0.04, respectively). In left lungs of IR animals, VCV increased the expression of interleukin-6 and intercellular adhesion molecule-1 compared to NV, with no significant differences between VV and NV. Compared to VCV, VV increased the expression of surfactant protein-D, suggesting protection from type II epithelial cell damage. In conclusion, in this experimental lung ischemia-reperfusion model, VV improved respiratory system elastance and reduced lung damage compared to VCV.